Power to the People: Data Citizens in the Age of Precision Medicine - Evans, Barbara J. (Vanderbilt J Entertain Technol Law, 2017)
Twentieth-century bioethics celebrated individual autonomy but framed autonomy largely in terms of an individual’s power to make decisions and act alone. The most pressing challenges of big data science in the twenty-first century can only be resolved through collective action and common purpose. This Article surveys some of these challenges and asks how common purpose can ever emerge on the present bioethical and regulatory landscape. The solution may lie in embracing a broader concept of autonomy that empowers individuals to protect their interests by exercising meaningful rights of data citizenship. This Article argues that twentieth-century bioethics was a paternalistic, top-down affair in which self-proclaimed ethics experts set standards to protect research subjects portrayed as autonomous yet too vulnerable and disorganized to protect themselves. The time may be ripe for BioEXIT, a popular uprising of regular people seeking a meaningful voice in establishing citizen-led ethical and privacy standards to advance big-data science while addressing the concerns people feel about the privacy of their health data.